Electrolyte, lithium ion battery and preparation method thereof
By using a new electrolyte composed of 1,2,3-glycerol triacetate, vinyl carbonate and lithium salt in lithium-ion batteries, the problems of electrolyte evaporation and interface layer decomposition of lithium-ion batteries at high temperatures are solved, and the high temperature stability and safety of the battery are improved.
Patent Information
- Application Number
- CN202411944309.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
Existing lithium-ion batteries have problems such as electrolyte evaporation, solid electrolyte interface and positive electrode electrolyte interface layer decomposition at high temperatures, resulting in capacity attenuation and reduced safety.
A new electrolyte, including 1,2,3-glycerol triacetate, vinyl carbonate and lithium salt, is used to form an electrolyte system with high boiling point and stability through a specific volume ratio and molar ratio combination.
It significantly improves the stability and safety of the battery at high temperatures, extends the cycle life of the battery, and improves the high-temperature cycle performance of the battery cell.
Smart Images

Figure BDA0005213277430000071
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to an electrolyte, a lithium ion battery and a preparation method thereof. Background Art
[0002] Lithium-ion batteries with high energy density are a long-awaited product for industrial applications such as mining, grid stabilization, naval, aerospace, and medical devices. However, the safety, cycle life, energy density, and cost of available high-temperature battery technologies remain a hurdle. Batteries operating at higher temperatures generally experience faster capacity decay than batteries at lower temperatures, which is mainly attributed to three factors: electrolyte evaporation, decomposition of the solid electrolyte interface (SEI) and cathode electrolyte interface (CEI) layers, and cathode failure. At higher temperatures, conventional boiling electrolytes evaporate and decompose, resulting in localized dry electrode regions with high impedance. Such dry electrode regions lead to uneven current distribution and further to uneven lithium ion deposition. Negative and positive electrode surface layers also decompose at elevated temperatures, especially organic components. Fresh negative / positive electrode surface exposure will promote electrode reactions and generate thicker SEI / CEI layers, exacerbating electrolyte consumption. In addition, at higher temperatures, the cathode active materials also play an important role in capacity decay. With increasing temperature, most cathode materials become less stable, exacerbating the transition metal ion dissolution problem when they leave their native structure.
[0003] The transition metal dissolution problem not only leads to the pulverization of active materials, but also catalyzes the decomposition of the electrolyte, eventually leading to complete battery failure at high temperatures. In addition, the self-discharge problem becomes more serious at high temperatures because the mobility of lithium ions is also higher and will also lead to capacity decay. In order to improve the high temperature performance of the battery, better electrolyte systems with higher boiling points and stability are needed to help us understand the battery failure mechanism at higher temperatures and achieve safer applications. Long-term storage at high temperatures is also another challenge for energy storage batteries. Batteries stored at higher temperatures experience spontaneous electron diffusion from the cathode to the electrolyte, which triggers the decomposition of lithium salts and cathode degradation. SEI / CEI layer decomposition and reconstruction also consumes active lithium in the cell and causes irreversible capacity decay during long-term storage.
[0004] Therefore, it is urgent to develop a new type of high-temperature electrolyte solvent to solve the above problems in order to improve the storage performance and safety of energy storage cells. Summary of the invention
[0005] Based on the defects of the prior art, the first purpose of the present invention is to provide an electrolyte; the second purpose of the present invention is to provide a method for preparing the electrolyte; the third purpose of the present invention is to provide an application of the electrolyte in the preparation of a lithium ion battery; the fourth purpose of the present invention is to provide a lithium ion battery comprising the electrolyte; the fifth purpose of the present invention is to provide a method for preparing the lithium ion battery.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] On the one hand, the present invention provides an electrolyte, which includes: 1,2,3-propylene glycol triacetate, ethylene carbonate and lithium salt; wherein the volume ratio of the 1,2,3-propylene glycol triacetate to the ethylene carbonate is (0.8-1):(0.8-1); the amount ratio of the lithium salt to the 1,2,3-propylene glycol triacetate is (1-1.8) mol:100 mL.
[0008] In the above electrolyte, preferably, the ethylene carbonate is selected from ethylene carbonate and / or fluoroethylene carbonate; but not limited thereto.
[0009] In the above electrolyte, preferably, the lithium salt is selected from one or more combinations of lithium hexafluorophosphate, lithium bis(fluoromethanesulfonyl)imide and lithium difluorooxalatoborate; but not limited thereto.
[0010] On the other hand, the present invention also provides a method for preparing the above-mentioned electrolyte, which comprises the following steps:
[0011] 1,2,3-propanetriol triacetate and ethylene carbonate are mixed to obtain a mixed solution; lithium salt is added to the mixed solution, and the mixture is stirred evenly to obtain an electrolyte.
[0012] In another aspect, the present invention also provides use of the above electrolyte in preparing a lithium ion battery.
[0013] In another aspect, the present invention further provides a lithium-ion battery comprising a positive electrode, a negative electrode and the above-mentioned electrolyte.
[0014] In the above-mentioned lithium-ion battery, preferably, the positive electrode is composed of a nickel-cobalt-manganese oxide positive electrode material, conductive carbon black, polyvinylidene fluoride and carbon nanotubes, or is composed of a lithium iron phosphate positive electrode material, conductive carbon black and polyvinylidene fluoride.
[0015] In the above-mentioned lithium-ion battery, preferably, the weight ratio of the nickel-cobalt-manganese oxide positive electrode material, the conductive carbon black, the polyvinylidene fluoride and the carbon nanotubes is (96-97): (1.8-2): (1.7-2): (0.5-1).
[0016] In the above-mentioned lithium-ion battery, preferably, the weight ratio of the lithium iron phosphate positive electrode material, the conductive carbon black and the polyvinylidene fluoride is (96-97)(1-2)(1.5-2).
[0017] In the above-mentioned lithium-ion battery, preferably, the mass distribution of the positive electrode is 16.0 mg / cm on each side. 2 .
[0018] In the above-mentioned lithium-ion battery, preferably, the negative electrode is composed of graphite, silicon-carbon negative electrode binder, conductive carbon black, polyvinylidene fluoride and carbon nanotubes.
[0019] In the above-mentioned lithium-ion battery, preferably, the weight ratio of the graphite, the silicon-carbon negative electrode binder, the conductive carbon black, the polyvinylidene fluoride and the carbon nanotube is 96:2.3:0.9:0.4:0.4.
[0020] In the above lithium-ion battery, preferably, the capacity ratio N / P value of the negative electrode to the positive electrode is 1.13.
[0021] In the above lithium-ion battery, preferably, the mass distribution of the negative electrode is 10.1 mg / cm on each side. 2 .
[0022] In the above lithium-ion battery, preferably, the lithium-ion battery further comprises a separator, a positive electrode current collector and a negative electrode current collector.
[0023] In the above lithium-ion battery, preferably, the separator is made of polyethylene film.
[0024] In the above lithium-ion battery, preferably, the positive electrode current collector is made of 13+1+1 μm aluminum foil.
[0025] In the above lithium-ion battery, preferably, the negative electrode current collector is made of 6.0 μm copper foil.
[0026] On the other hand, the present invention also provides a method for preparing the above-mentioned lithium-ion battery, which comprises assembling the positive electrode, the negative electrode and the above-mentioned electrolyte according to the assembly method of the lithium-ion battery, and optionally further comprising assembling a separator, a positive electrode current collector and a negative electrode current collector.
[0027] Beneficial effects of the present invention:
[0028] (1) The present invention uses 1,2,3-propanetriol triacetate as a solvent in an electrolyte system to increase the temperature of the thermal decomposition of the electrolyte from 80°C to 130°C, which greatly reduces the heat generation during thermal runaway of the battery cell, improves the safety of the battery cell, and can increase the stable cycle temperature of the battery cell to 80°C.
[0029] (2) The electrolyte of the present invention has excellent stability and compatibility with positive and negative electrodes at high temperatures.
[0030] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail below. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The process, conditions, reagents, experimental methods, etc. for implementing the present invention, except for the contents specifically mentioned below, are all common knowledge and common common sense in the art, and the present invention does not particularly limit the contents.
[0032] Embodiment 1:
[0033] This embodiment provides an electrolyte and a preparation method thereof, the preparation method comprising the following steps:
[0034] (1) 100 mL of 1,2,3-propanetriol triacetate and 100 mL of ethylene carbonate were mixed to obtain a mixed solution.
[0035] (2) Add 1 mol of lithium difluorooxalatoborate to the mixed solution and stir evenly to obtain an electrolyte.
[0036] This embodiment also provides a lithium-ion battery assembled using the above electrolyte, which is as follows:
[0037] (1) Positive electrode (16.0 mg / cm on each side) 2 ): It is composed of LFP, SuperP, and PVDF 5130 in a weight ratio of 97:1:2. 13+1+1um aluminum foil is used as the positive electrode current collector.
[0038] (2) Negative electrode (10.1 mg / cm on each side) 2 ): It is composed of graphite, LA136D, SuperP, CNT and CMC in a weight ratio of 96:2.3:0.9:0.4:0.4. The N / P value is close to 1.13. Copper foil with a thickness of 6.0μm is used as the negative electrode current collector.
[0039] (3) Diaphragm: Ceramic-coated polyethylene film.
[0040] (4) Electrolyte: The electrolyte prepared in this example is used.
[0041] The battery is assembled according to the conventional assembly method of lithium-ion batteries.
[0042] Embodiment 2:
[0043] This embodiment provides an electrolyte and a preparation method thereof, the preparation method comprising the following steps:
[0044] (1) 100 mL of 1,2,3-propanetriol triacetate and 100 mL of fluoroethylene carbonate were mixed to obtain a mixed solution.
[0045] (2) Add 1 mol of lithium difluorooxalatoborate to the mixed solution and stir evenly to obtain an electrolyte.
[0046] This embodiment also provides a lithium-ion battery assembled using the above electrolyte, which is as follows:
[0047] (1) Positive electrode (16.0 mg / cm on each side) 2 ): It is composed of LFP, Super P, and PVDF 5130 in a weight ratio of 97:1:2. 13+1+1um aluminum foil is used as the positive electrode current collector.
[0048] (2) Negative electrode (10.1 mg / cm on each side) 2 ): It is composed of graphite, LA136D, SuperP, CNT and CMC in a weight ratio of 96:2.3:0.9:0.4:0.4. The N / P value is close to 1.13. Copper foil with a thickness of 6.0μm is used as the negative electrode current collector.
[0049] (3) Diaphragm: Ceramic-coated polyethylene film.
[0050] (4) Electrolyte: The electrolyte prepared in this example is used.
[0051] The battery is assembled according to the conventional assembly method of lithium-ion batteries.
[0052] Embodiment 3:
[0053] This embodiment provides an electrolyte and a preparation method thereof, the preparation method comprising the following steps:
[0054] (1) 100 mL of 1,2,3-propanetriol triacetate and 100 mL of ethylene carbonate were mixed to obtain a mixed solution.
[0055] (2) Add 1 mol of lithium hexafluorophosphate to the mixed solution and stir evenly to obtain an electrolyte.
[0056] This embodiment also provides a lithium-ion battery assembled using the above electrolyte, which is as follows:
[0057] (1) Positive electrode (16.0 mg / cm on each side) 2 ): It is composed of LFP, SuperP, and PVDF 5130 in a weight ratio of 97:1:2. 13+1+1um aluminum foil is used as the positive electrode current collector.
[0058] (2) Negative electrode (10.1 mg / cm on each side) 2 ): It is composed of graphite, LA136D, SuperP, CNT and CMC in a weight ratio of 96:2.3:0.9:0.4:0.4. The N / P value is close to 1.13. Copper foil with a thickness of 6.0μm is used as the negative electrode current collector.
[0059] (3) Diaphragm: Ceramic-coated polyethylene film.
[0060] (4) Electrolyte: The electrolyte prepared in this example is used.
[0061] The battery is assembled according to the conventional assembly method of lithium-ion batteries.
[0062] Comparative Example 1:
[0063] As a control, this comparative example uses a lithium-ion battery assembled with a conventional electrolyte, specifically as follows:
[0064] (1) Positive electrode (16.0 mg / cm on each side) 2 ): It is composed of LFP, Super P, and PVDF 5130 in a weight ratio of 97:1:2. 13+1+1um aluminum foil is used as the positive electrode current collector.
[0065] (2) Negative electrode (10.1 mg / cm on each side) 2 ): It is composed of graphite, LA136D, SuperP, CNT and CMC in a weight ratio of 96:2.3:0.9:0.4:0.4. The N / P value is close to 1.13. Copper foil with a thickness of 6.0μm is used as the negative electrode current collector.
[0066] (3) Diaphragm: Ceramic-coated polyethylene film.
[0067] (4) Electrolyte: 1M LiPF6 / EC:DEC:DMC=1:1:1 (v / v / v) was used as the electrolyte.
[0068] The battery is assembled according to the conventional assembly method of lithium-ion batteries.
[0069] Comparative Example 2:
[0070] As a control, this comparative example uses a lithium-ion battery assembled with a conventional electrolyte, specifically as follows:
[0071] (1) Positive electrode (16.0 mg / cm on each side)2 ): It is composed of LFP, Super P, and PVDF 5130 in a weight ratio of 97:1:2. 13+1+1um aluminum foil is used as the positive electrode current collector.
[0072] (2) Negative electrode (10.1 mg / cm on each side) 2 ): It is composed of graphite, LA136D, SuperP, CNT and CMC in a weight ratio of 96:2.3:0.9:0.4:0.4. The N / P value is close to 1.13. Copper foil with a thickness of 6.0μm is used as the negative electrode current collector.
[0073] (3) Diaphragm: Ceramic-coated polyethylene film.
[0074] (4) Electrolyte: 1 M LiODFB / EC:DEC:DMC=1:1:1 (v / v / v) was used as the electrolyte.
[0075] The battery is assembled according to the conventional assembly method of lithium-ion batteries.
[0076] Test experiment:
[0077] Differential scanning calorimetry (DSC) was used under nitrogen with a heating rate of 2.5°C / min and the mass of each test sample was 10 mg. Thermogravimetric analysis (TGA) was used under nitrogen with a heating rate of 5°C / min.
[0078] Cyclic voltammetry (CV) tests were performed using a three-electrode system with two platinum sheets as working and counter electrodes and a lithium metal electrode as a reference electrode. Each electrolyte was scanned at a scan rate of 0.01 mV / s at 25 °C from 4.5 V to 0 V vs Li / Li + The working window of NCM523 cell cycle test is 3.0~4.3V vs Li / Li + , LFP cell is 2.5~4.0V vs Li / Li + .
[0079] The performance test results are shown in Table 1 below.
[0080] Table 1:
[0081]
[0082] It can be seen from the experimental results in Table 1 that: Through the DSC experimental data, it can be concluded that the electrolyte in the embodiment of the present invention has strong stability, and there is no obvious solvent decomposition before 130°C, while in the comparative example, a large amount of solvent begins to decompose under heat before 80°C. Through the TGA data, it can be concluded that the electrolyte in the embodiment has strong anti-volatility and is not easy to volatilize when stored at room temperature, while the conventional electrolyte in the comparative example is extremely volatile at room temperature, difficult to store, and high in cost. Through the CV data, it can be concluded that both the embodiment and the comparative example have an electrochemical window of up to 4.5V. Through the cycle data, it can be concluded that the embodiment has excellent cycle performance, and the electrolyte of the present invention can greatly improve the high-temperature cycle performance of the battery cell, and through all the above experimental data, the electrolyte of the present invention can greatly improve the safety performance of the battery cell, and the probability of thermal runaway of the battery cell is greatly improved.
[0083] The present invention uses specific embodiments to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. An electrolyte, characterized in that: The electrolyte includes: 1,2,3-propylene glycol triacetate, ethylene carbonate and lithium salt; wherein the volume ratio of the 1,2,3-propylene glycol triacetate to the ethylene carbonate is (0.8-1):(0.8-1); and the amount ratio of the lithium salt to the 1,2,3-propylene glycol triacetate is (1-1.8) mol:100 mL.
2. The electrolyte according to claim 1, characterized in that The ethylene carbonates are selected from ethylene carbonate and / or fluoroethylene carbonate.
3. The electrolyte according to claim 1, characterized in that: The lithium salt is selected from the group consisting of one or more of lithium hexafluorophosphate, lithium bis(fluoromethanesulfonyl)imide and lithium difluorooxalatoborate.
4. The method for preparing the electrolyte according to any one of claims 1 to 3, comprising the following steps: 1,2,3-propanetriol triacetate and ethylene carbonate are mixed to obtain a mixed solution; lithium salt is added to the mixed solution, and the mixture is stirred evenly to obtain an electrolyte.
5. Use of the electrolyte according to any one of claims 1 to 3 or the electrolyte prepared by the preparation method of claim 4 in the preparation of lithium-ion batteries.
6. A lithium ion battery comprising a positive electrode, a negative electrode and the electrolyte according to any one of claims 1 to 3.
7. The lithium-ion battery according to claim 6, characterized in that: The positive electrode is composed of a nickel-cobalt-manganese oxide positive electrode material, conductive carbon black, polyvinylidene fluoride and carbon nanotubes, or a lithium iron phosphate positive electrode material, conductive carbon black and polyvinylidene fluoride; Preferably, the weight ratio of the nickel-cobalt-manganese oxide positive electrode material, the conductive carbon black, the polyvinylidene fluoride and the carbon nanotube is (96-97): (1.8-2): (1.7-2): (0.5-1); Preferably, the weight ratio of the lithium iron phosphate positive electrode material, the conductive carbon black and the polyvinylidene fluoride is (96-97)(1-2)(1.5-2); Preferably, the mass distribution of the positive electrode is 16.0 mg / cm on each side. 2 .
8. The lithium-ion battery according to claim 6, characterized in that The negative electrode is composed of graphite, silicon-carbon negative electrode binder, conductive carbon black, polyvinylidene fluoride and carbon nanotubes; Preferably, the weight ratio of the graphite, the silicon-carbon negative electrode binder, the conductive carbon black, the polyvinylidene fluoride and the carbon nanotube is 96:2.3:0.9:0.4:0.4; Preferably, the capacity ratio N / P value of the negative electrode relative to the positive electrode is 1.13; Preferably, the mass distribution of the negative electrode is 10.1 mg / cm on each side. 2 .
9. The lithium-ion battery according to claim 6, characterized in that: The lithium-ion battery also includes a separator, a positive electrode current collector and a negative electrode current collector; Preferably, the diaphragm is made of polyethylene film; Preferably, the positive electrode current collector is made of 13+1+1 μm aluminum foil; Preferably, the negative electrode current collector is made of 6.0 μm copper foil.
10. A method for preparing a lithium-ion battery according to any one of claims 6 to 9, comprising assembling a positive electrode, a negative electrode and the electrolyte according to any one of claims 1 to 3 according to an assembly method for a lithium-ion battery, and optionally further comprising assembling a separator, a positive electrode current collector and a negative electrode current collector.